Antisipasi terhadap Penyebaran Hoaks Perspektif Al-Quran: Analisis pada Surah An-Nur Ayat 11 - Nashrullah Nashrullah; Ahmad Yusam Thobroni (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
The spread of hoaxes is one of the growing social challenges in the digital age, especially when information can spread widely without adequate verification. The Quran, as a source of ethics and guidance for life, provides important principles for addressing this phenomenon. Surah an-Nur verse 11, which recounts the story of the hadis ifki (false news) attributed to Aisya r.a, offers a moral and methodological framework for understanding the dangers of slander and how to anticipate it. This study aims to analyze this verse using a thematic and tafsīr maudhū’i approach in order to explore the values of the Quran related to caution in receiving news, verifying information, and the prohibition of spreading information that has not been proven to be true. The results of the study show that this verse not only emphasizes spiritual and ethical aspects, but also provides a concept of communication that is relevant to the current context. These principles of the Quran can be used as a foundation for building digital literacy and ethics in the use of social media, so that the public is able to anticipate and prevent the spread of hoaxes more effectively.